How Serious Do We Need to Be? Improving Information Literacy Skills through Gaming and Interactive Elements - van Meegen, Ana; Limpens, Imke (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Catching the attention of highly technologically and visually oriented students is a challenge for libraries. The number of students entering the universities is increasing and a face-to-face learning setting is an impossible mission for the few available subject librarians. This paper demonstrates how effective the use of serious game or other web-based interactive elements can be for teaching information literacy. By means of quasi-experimental research the impact that the game Saving Asia on students’ learning is analysed and compared to a web-based online tutorial of the Vrije Universiteit Amsterdam (Free University of Amsterdam). This research demonstrated that the game needs to be improved if it is to fit into the regular curriculum of the university, but interactive elements definitely improve learning results.